Analisis Kinerja Penyuluh Keluarga Berencana di Kelurahan Sidorame Timur Kecamatan Medan Perjuangan - Damanik, Maharani Iviola adithia; Muda, Indra; Lubis, Yurial Arief (Universitas Medan Area, 2024)
East Sidorame Village is a village that runs a family planning program can be run with a family planning instructor who assists in monitoring and fostering the family planning program. The problem this study is the performance of family planning instructors and the factors that hinder the performance of family planning instructors in the East Sidorame Village, Medan Perjuangan District. Data collection is done through observation, interviews and documentaries. This research usues qualitative method with a descriptive approach. The results showed that the performance of family planning instructors in the East Sidorame Village, Medan Perjuangan District was good. Judging from the performance indicatorsused, namely in terms of quality, effectiveness, timeliness and work commitment related to ability, knowledge, the method used to complete the report, the responsibilities and loyalty of the family planning instructor are appropriate. In terms of independence and quantity, extension workers continue to receive assistance in conducting counseling and the target of counseling has not been evenly distributed to community due to the covid-19 pandemic. The obstacle to the performance of family planning instructors in the East Sidorame Village, Medan Perjuangan District, is that the Counseling has not been maximized and evenly distributed due to the covid-19 pandemic, so that the target for PUS participating in the family planning program has not been achieved.